The Emergence of the "Prerrexurdentismo" through the Will of the Didacticism of the Nineteenth-Century Galician Literature: the "Himno Gallego a S.M. la Reina Doña Isabel 2ª", by Vicente de Turnes - Pardo de Neyra, Xulio (Madrygal. Revista de Estudios Gallegos, 2017)
By focusing on a nineteenth-century Galician hymn, written and published in the mid-nineteenth century by Vicente de Turnes, this study analyzes the vocation of a literature that is aware of its role in the institutionalization of a movement which clearly defines its quality: the Rexurdimento. In this mission, its didactic interest reveals how, from the space of circumstance, in 19th century Galiza a commitment develops which, from popularism, is tied up with the most obvious didacticism.
Keywords: Galician Literature; Prerrexurdentismo; Didactics of Galician Literature; Literary Criticism; Vicente Turnes.